City of scoundrels [compact disc, unabridged] : the twelve days of disaster that gave birth to modern Chicago - Krist, Gary (Books on Tape, 2012)
Summer 1919: the city of Chicago seemed on the verge of transformation. Modernizers had an audacious, expensive plan to turn the city from a brawling, unglamorous place into 'the Metropolis of the World.' But just as the dream seemed within reach, pandemonium broke loose--the city's highest ambitions suddenly under attack by the same unbridled energies that had given birth to them in the first place.